2015
DOI: 10.1108/jaee-06-2012-0024
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social and environmental disclosure and corporate performance

Abstract: Purpose – The purpose of this paper is to investigate the relationship between corporate performance and social and environmental disclosure for two African leading countries namely, South Africa (common law country) and Morocco (civil law country). Design/methodology/approach – The sample consists of 168 annual reports spanning from 2004 to 2009. A content analysis of companies’ annual reports is used to measure the extent of voluntary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
115
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 49 publications
15
115
0
4
Order By: Relevance
“…Such companies are thus likely to experience more pressure from consumers, government bodies and other stakeholders (both local and otherwise). These observations could justify the broader use of GRI indicators and confirm the results of other studies that showed that sector can affect CSR reporting [40,41].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Such companies are thus likely to experience more pressure from consumers, government bodies and other stakeholders (both local and otherwise). These observations could justify the broader use of GRI indicators and confirm the results of other studies that showed that sector can affect CSR reporting [40,41].…”
Section: Discussionsupporting
confidence: 75%
“…These studies showed opposing results [36][37][38]. A company's sector affiliation with a "sensitive" sector is a variable capable of influencing socio-environmental disclosure [39][40][41].…”
Section: Gri Performance Indicators and Their Determinantsmentioning
confidence: 94%
“…Although these studies had different results, the majority concluded that corporate social responsibility disclosure has a positive impact on business efficiency. Several studies had reported negative results Makni et al (2009) and in some cases there were not statistically significant Strouhal et al (2015), Khlif et al (2015), Tjia& Setiawati (2012). In Vietnam, some studies have investigated the current state and benefits of corporate social responsibility disclosure.…”
Section: Productsmentioning
confidence: 99%
“…CSR disclosures may affect corporate financial performance through several crucial aspects: increased employees' motivation and productivity, increased products' acceptance among customers, increased acceptance among investors who support social or environmental values. Overall, the expected benefits of CSR disclosures may largely exceed their costs implying higher corporate financial performance (Khlif et al, 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%